Allen Carr's Easyway to Stop Smoking - A randomised clinical trial. Issue 4 (25th October 2018) - Keogan, Sheila; Li, Shasha; Clancy, Luke
Abstract : Objective: To determine if Allen Carr's Easyway to Stop Smoking (AC) was superior to Quit.ie in a randomised clinical trial (RCT). Setting: Single centre, open RCT, general population based. Participants: 300 adult smokers, 18 years plus, minimum 5 cigarettes daily, and English speaking. AC, 151 (females 44.4%) and Quit.ie, 149 (females 45.6%), mean age 44 years. outcomes for all 300 were analysed (intention-to-treat). Recruited through advertisement from July 2015 to February 2016. Intervention: Randomly assigned to AC (n=151) and Quit.ie (n=149), matched for age, sex and education. Block randomisation, enrolment and follow-up at 1, 3, 6 and 12 months. Primary aim was to determine if AC had higher quit rates than Quit.ie service at 3 months. Secondary aims: quit rates at 1, 6 and 12 months and analysis of associated factors including weight. AC consisted of a 5-hour seminar, in a group setting. Quit.ie is an online portal for smoking cessation. Results: AC had higher quit rates at 1, 3, 6 and 12 months. AC: 38%, (n=57), 27% (n=40), 23% (n=35), 22% (n=33) vs Quit.ie: 20% (n=30), 15% (n=22), 15% (n=23), 11% (n=17), respectively (all p values <0.05). Logistic regression AC vs Quit.ie, OR 2.26 (95% CI 1.22 to 4.21) p value=0.01. Weight gain 3.8 kg in AC vs 1.8 kg in Quit.ie (p value <0.05). Conclusions: All AC quit rates were superior to Quit.ie, outcomes were comparable with established interventions. Trial registration number: ISRCTN12951013 . Recruitment July 2015–February 2016.